FROM KNOWLEDGE TO CARE: UNDERSTANDING MENSTRUAL HYGIENE PRACTICES AMONG PUBLIC HEALTH STUDENTS - Ivena, Pinaka Dya; Salsabilathifa, Nasywa Zuriah; Bahira, Hajar; Imelda, Laela Vita; Wulandari, Anggun Putri; Kinanti, Novita Cahya; Kusumawardani, Devi Arine (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Menstrual disorders vary among adolescents between 23% and 76% which can negatively impact adolescents’ health, academic success, and extracurricular activities. Knowledge and menstrual hygiene practices are important factors that influence seeking health services. This study aimed to assess students' knowledge and menstrual hygiene practices at the Faculty of Public Health, University of Jember, and to analyze the correlation between the level of knowledge and menstrual hygiene practices and the menstrual cycle of Public Health students. Method: This cross-sectional study was performed on female students at the Faculty of Public Health, University of Jember, classes of 2021, 2022, and 2023. This study was conducted from June to August 2024. A total of 150 public health students were recruited by simple random sampling. The public health students were interviewed using the questionnaire, and the data were analyzed using univariate and bivariate analyses using the chi-square test. Result: The study found that more than half (65,3%) of female students had poor knowledge about menstrual hygiene, while only 54,7% demonstrated good menstrual hygiene practices. The analysis showed no correlation between the knowledge levels and menstrual hygiene practices with the menstrual cycle among public health students at the University of Jember. Conclusion: These findings underscore the low level of knowledge and menstrual hygiene practices among the respondents, emphasizing the urgent need for action and the urgency of enhancing awareness about adopting good menstrual hygiene practices, organizing meetings with the female students, and the importance of community support in addressing this issue